Synthesis, Biological Activity, and Molecular Docking Studies of Novel 5‐Substituted‐1, 2, 4‐Triazole‐3‐thione Derivatives. Issue 6 (13th February 2020) - Qi, Le; Wu, Shao‐Jie; Li, Mou‐Cui; Bai, Jia‐Chao; Ma, Hai‐Xia; Ren, Ying‐Hui
Abstract: Seven Schiff base compounds were synthesized via the nucleophilic condensation of 5‐substituted‐3‐thione‐1, 2, 4‐triazole and 2, 4, 6‐trimethyl benzaldehyde. All of the synthesized compounds (A1 –A3 and B1 –B4 ) were thoroughly characterized by using spectroscopic and physical analytical methods. The in vitro antifungal activities of the prepared compounds were studied, and results showed that A2, B1, B2, and B3 have good biological activity. Molecular docking was used to predict the binding modes of the ligands to 6CR2 protein, and the reasons behind the excellent activities of A2 and B2 were explored. Finally, the highest occupied molecular orbital, lowest unoccupied molecular orbital, and natural bonding orbital of the compounds were calculated by using density functional theory at the B3LYP/6‐31G level. Abstract : Seven Schiff base compounds were synthesized and characterized by IR, 1 H NMR, and EA. A3 was also characterization by XRD. The biological activity of the title compounds against five fungi was determined, and the binding mode between 6CR2 protein and the ligands was predicted by molecular docking. A2, B1, B2, and B3 exhibited good activity against Wheat gibberellic, G. cingulata, and Maize rough dwarf bacteria . The DFT method was used to assess the biological activity of these compounds.